Uso de biomassa e de carvão vegetal em gaseificadores para produzir gás adequado a motores de combustão interna - Claudino Filho, Vicente de Vasconcelos (2019)
Meeting today’s demand for energy is one of society’s great challengers. Each day the curve that demonstrate how much energy is consume around the world has risen in a faster rate than the sources can generate. Industry development and residential consumption are the key drivers for this. A way to try to meet this demand is the using of renewable energy sources. However, many of the renewable sources depends exclusively on climatic factors, such as wind and sun. Biomass gasification may be a way out to avoid this dependence. Biomass it is a resource available throughout the year, without being hamper by climatic factors. In turn, the use of residual biomass prevents pollution of the environment, while transforming it into an alternative source of energy. The goal of the present work is to show that is possible in an efficient way to generate electricity from waste wood, and posteriorly charcoal, using a gasifier that has 8 kWt of generation capacity and a genset linked to a Otto Cycle engine. A resistive charge simulator made up of bulb lamps with power ratings ranging from 150 to 280 W, making 2.04 kW. The goals of the present work, it was successfully achieved. By replacing the in natura biomassa with charcoal it was possible to increase the efficiency of the gasifier/genset,. Moreover, it can be seen reduction on biomassa specific consumption (charcoal) of the gasifier. The resistive charge simulator worked as expected , had been possible to activate all eight bulb lamps, getting, thus, the maximum work power from engine. It was found, in the other hand, by replacing the in natura biomass with charcoal it convenient to the system conservation status, eliminating the harmful effects the tar causes to piping apparatus. This importance make more notorious, when there is not adherence and immobilization of parts of internal combustion engine, like valves and pistons. Thus, another step is taken to demonstrate the viability of biomass gasification as an alternative energy source, among those existing in the national scenario.